2020
DOI: 10.5187/jast.2020.62.5.648
|View full text |Cite
|
Sign up to set email alerts
|

Improving sugarcane bagasse quality as ruminant feed with Lactobacillus, cellulase, and molasses

Abstract: The objective of the study was to evaluate the effects of Lactobacillus, cellulase, and molasses on chemical composition, fermentation qualities, and microorganism count of sugarcane bagasse silage after 30-days fermentation. The treatments were arranged according to a factorial arrangement (2 × 2 × 2) + 1, in a complete randomized design. The first factor consisted of two levels of Lactobacillus casei TH14 (TH14, 0 and 0.05 g/kg fresh matter; the second factor consisted of two levels of cellulase enzyme (C, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
1
19
0
2
Order By: Relevance
“…Compared with the control group, the content of lactic acid bacteria in the additive treatment group increased by 12.4–17.9%, and the growth of non-important bacteria was inhibited. The physiological growth of L and an adequate supply of M as a substrate could explain an increase in L count ( So et al, 2020 ). Control silage had no satisfactory microorganisms (e.g., aerobic bacteria and yeasts), while the addition treatments dramatically reduced the counts of aerobic bacteria and molds.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the control group, the content of lactic acid bacteria in the additive treatment group increased by 12.4–17.9%, and the growth of non-important bacteria was inhibited. The physiological growth of L and an adequate supply of M as a substrate could explain an increase in L count ( So et al, 2020 ). Control silage had no satisfactory microorganisms (e.g., aerobic bacteria and yeasts), while the addition treatments dramatically reduced the counts of aerobic bacteria and molds.…”
Section: Discussionmentioning
confidence: 99%
“…After mixing, the SB was placed in plastic bags (24 × 42 × 180 cm, 11-mm thick), manually pressed to remove the inner air, and anaerobically fermented for 30-days. The qualities of SB fermentation (So et al, 2020a) are presented in Table 1. The BG was adjusted with RS at different ratios (100:0, 80:20, 60:40, 40:60, 20:80, 0:100; RS: fermented SB) for 21 days to make sure that steers could completely adapt to the new roughage source.…”
Section: Rice Straw and Preparation Of Sb Fermentationmentioning
confidence: 99%
“…In accordance with this, Keawpila et al [33] reported the numbers of yeast were reduced by LAB inoculation in silage. Accordingly, the ensiling additive with L. casie TH14, cellulase, and molasses in combination has resulted in the promotion of the best qualities of rice straw and sugarcane bagasse, respectively [68,69]. In addition, the combination of LAB and enzymes resulted in a faster pH decrease, which enhanced both the fermentation quality and the aerobic stability of tomato pomace and pumpkin silage [70].…”
Section: Microbiology and Aerobic Stability Of Cassava Pulp Treated W...mentioning
confidence: 99%